'Hollering from across the yard': fictive path in manner of speaking events*. (23rd April 2014) - VERGARO, CARLA; SANDFORD, JODI L.; MASTROFINI, ROBERTA; FORMISANO, YHARA M.
Abstract : The aim of this study is to see how and to what extent the Talmyan notion of fictive motion is realized in the conceptual frame of speaking. Drawing from a previous in-depth analysis of the speaking event Manner component in English (cf. Vergaro, Sandford, Mastrofini, and Formisano, unpublished observations), 1 we investigate the realization of fictive path in 186 English manner of speaking (henceforth MoS) verb entries accessed through the Corpus of Contemporary American English (henceforth COCA). Fictive path is always involved in the conceptualization of the speaking event. Communication is elaborated through theconduit metaphor, which is, in turn, motivated by the embodied act of speaking. Fictive path is further considered in relation to image schemas and windowing. Different degrees of path windowing emerge from this study, illustrating how the speaker focuses attention on a specific portion of the speaking event. Image schema distribution and an implicational hierarchy of the various types of path elaboration also become evident in this study.